2005
DOI: 10.3171/jns.2005.102.2.0311
|View full text |Cite
|
Sign up to set email alerts
|

Pressure reactivity as a guide in the treatment of cerebral perfusion pressure in patients with brain trauma

Abstract: Based on data from this study, the authors concluded that ICP-oriented therapy should be used in patients whose slope of the MABP/ICP regression line is at least 0.13, that is, in pressure-passive patients. If the slope is less than 0.13, then hypertensive CPP therapy is likely to produce a better outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(126 citation statements)
references
References 20 publications
2
120
1
2
Order By: Relevance
“…Patients with impaired autoregulation, with a PRx slope > 0.13, may have a better outcome with hypotensive ICP-oriented therapy, such as the Lund protocol. 22 As mentioned above, this observation has been incorporated into the most recent guidelines for the management of severe TBI. 7,8 The normal 100 mm Hg-wide sROR range (50-150 mm Hg) can be reduced to a 10 mm Hg-wide autoregulation range in severe TBI.…”
Section: Diagnosis Of Abnormal Cerebral Autoregulation and Its Role Imentioning
confidence: 99%
“…Patients with impaired autoregulation, with a PRx slope > 0.13, may have a better outcome with hypotensive ICP-oriented therapy, such as the Lund protocol. 22 As mentioned above, this observation has been incorporated into the most recent guidelines for the management of severe TBI. 7,8 The normal 100 mm Hg-wide sROR range (50-150 mm Hg) can be reduced to a 10 mm Hg-wide autoregulation range in severe TBI.…”
Section: Diagnosis Of Abnormal Cerebral Autoregulation and Its Role Imentioning
confidence: 99%
“…The most readily available measure is the pressure reactivity index (PRx), which is a moving correlation coefficient calculated from measurements of ICP and MAP (Czosnyka et al 1998). Centers that employ this measurement have reported that patients with intact autoregulation (PRx is low) have improved outcomes when managed according to a CPP guided paradigm, whereas those with impaired autoregulation (PRx is elevated) benefit from an ICP targeted strategy (Howells et al 2005). Clearly, this observation warrants additional study.…”
Section: Cerebral Edema Intracranial Hypertension and Cerebral Perfumentioning
confidence: 99%
“…However, the physiological and pathophysiological significance of these phases has been debated, and significant regional variation of cerebral perfusion is present (Wintermark et al 2004). As discussed previously, cerebral perfusion can be significantly affected by systemic factors that impact the MAP and the CPP; the magnitude of this effect is dependent upon the individual's autoregulatory status (Czosnyka et al 1998;Howells et al 2005). Furthermore, the reports of the incidence and significance of cerebral vasospasm after trauma are variable, and likely are affected by the mechanism of injury (Martin et al 1997;Zubkov et al 2000).…”
Section: Cerebral Blood Flow and Brain Tissue Oxygenationmentioning
confidence: 99%
“…Of these models, the pressure reactivity index (PRx) is the most studied and uses the naturally occurring slow oscillations of ABF to estimate cerebrovascular reactivity. This is a moving correlation coefficient between 40 consecutive values of ABP and ICP averaged over 5 s. Studies [21,22] have established a correlation between PRx values of >0.2 for more than 6 h and a fatal outcome. Although it has its limitations, it has been found to be a reliable index of cerebral autoregulation validated by TCD and PET and can be used to guide therapy with the calculation of an optimal CPP or an individualized or patient-specific ICP.…”
Section: Pressure Reactivity Indexmentioning
confidence: 99%